Spatial and temporal dynamics of suspended sediment concentrations in coastal waters of the South China Sea, off Sarawak, Borneo: ocean colour remote sensing observations and analysis - Choo, Jenny (2023)
High-quality ocean colour observations are increasingly accessible to support various monitoring and research activities for water quality measurements. In this paper, we present a newly developed regional total suspended solids (TSSs) empirical model using MODIS Aqua's Rrs(530) and Rrs(666) reflectance bands to investigate the spatial and temporal variation in TSS dynamics along the southwest coast of Sarawak, Borneo, with the application of the Open Data Cube (ODC) platform. The performance of this TSS retrieval model was evaluated using error metrics (bias Combining double low line 1.0, MAE Combining double low line 1.47, and RMSE Combining double low line 0.22, in milligrams per litre) with a log10 transformation prior to calculation as well as using a k-fold cross-validation technique. The temporally averaged map of the TSS distribution, using daily MODIS Aqua satellite datasets from 2003 until 2019, revealed that large TSS plumes were detected - particularly in the Lupar and Rajang coastal areas - on a yearly basis. The average TSS concentration in these coastal waters was in the range of 15-20 mgL-1. Moreover, the spatial map of the TSS coefficient of variation (CV) indicated strong TSS variability (approximately 90 %) in the Samunsam-Sematan coastal areas, which could potentially impact nearby coral reef habitats in this region. Study of the temporal TSS variation provides further evidence that monsoonal patterns drive the TSS release in these tropical water systems, with distinct and widespread TSS plume variations observed between the northeast and southwest monsoon periods. A map of relative TSS distribution anomalies revealed strong spatial TSS variations in the Samunsam-Sematan coastal areas, while 2010 recorded a major increase (approximately 100 %) and widespread TSS distribution with respect to the long-term mean. Furthermore, study of the contribution of river discharge to the TSS distribution showed a weak correlation across time at both the Lupar and Rajang river mouth points. The variability in the TSS distribution across coastal river points was studied by investigating the variation in the TSS pixels at three transect points, stretching from the river mouth into territorial and open-water zones, for eight main rivers. The results showed a progressively decreasing pattern of nearly 50 % in relation to the distance from shore, with exceptions in the northeast regions of the study area. Essentially, our findings demonstrate that the TSS levels on the southwest coast of Sarawak are within local water quality standards, promoting various marine and socio-economic activities. This study presents the first observation of TSS distributions in Sarawak coastal systems with the application of remote sensing technologies and aims at enhancing coastal sediment management strategies for the sustainable use of coastal waters and their resources.